Role of Social Media in Enhancing Agricultural Growth - Singh, Gurdeep; Singh, Pritpal; Tiwari, Devinder; Singh, Kulwant (Indian Journal of Extension Education, 2021)
Social media has been extensively used by rural youth due to tremendous increase in the number of smart phones users during last decade. A survey was conducted during 2018-19 to study the use of social media as a source of agricultural information, use pattern, preference towards different modes of information receiving and sharing, and frequency of use among rural youth. The 200 rural youth were randomly selected from the South-Western Mansa district of Punjab. Results of the study revealed that only ~6 per cent of the young farmers were using Radio as source of information for agriculture. Majority of the young farmers preferred social media viz. Youtube, WhattsApp and Facebook as a source of agricultural information. The young farmers had subscribed agriculture based channels on YouTube for getting agriculture related information. Majority of young farmers had been maintaining 4-5 WhatsApp groups to share and receive information on agriculture and allied fields. Use of PAU Mobile App and Digital Newspaper (Kheti Sandesh) was also popular among farmers. Young farmers observed that use of social media has a significant impact on crop management practices. About one-fourth (~27%) of respondents had increased acreage under recommended crop varieties, ~16.5 per cent had reduced the average number of sprays on rice crop, ~22.5 per cent had been scheduling irrigation based on weather based agro-advisory and ~24.1 per cent were getting information on marketing of crops from social media.
Keywords: Mobile Apps; Digital media; Youtube; WhattsApp and Facebook